(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Hotel guests are ultimately seeking the best qualities to receive satisfactory and comfortable facilities during their stay and how internet and technology has fundamentally changed guests behaviour and their decision making processes for accommodation selection. In this era of digital development in technology guest have access to information through communication channels that are very much available at fingertips. Thus, the present study focuses on analysing the impact of social media marketing on guest’s hotel selection for a comfortable and satisfactory stay. Objectives: The objectives of the study were identification of social media marketing tools used by the different hotels and the impact of social media marketing on guest’s selection of hotel. Methodology: The questionnaire was distributed through Google Forms and responses were collected from 120 respondents from the state of Uttar Pradesh and Madhya Pradesh. Results: Most influential features on social media marketing in Guests selection of Hotel with 48% of responses are Location of the hotel (country, city, place etc.), Online Reviews & Feedback (40%) and Unique Selling Proposition of the hotel with 37% of responses (Special features). Conclusion: Social media marketing plays a pivotal role for hotels and business to build trust and establish credibility with their guests. In today’s scenario and age, it is a common tool for guests to research about hotels while choosing an accommodation and this is the reason, why social media marketing tools are so important.